Use of endophytic bacteria for the biological control of the Panamá disease (Fusarium oxysporum f.sp. cubense) in the cultivar Gros Michel (AAA) - Lara Fiallos, Diana F. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2009